Early return to work: Single-port vs. multiport laparoscopic surgery for benign ovarian tumor - Tang, Ying; Wen, Ming-bo; Su, Bin; Wang, Hang; Zheng, Xue-mei; Yang, Ming-tao; Yin, Shu; Xu, Fan; Hu, Hui-quan (Frontiers in Surgery, 2022)
Objective To compare the return to work (RTW) time between single-port laparoscopic surgery (SPLS) and multiport laparoscopic surgery (MPLS) for benign ovarian tumors. Methods A cross-sectional cohort study was conducted, which consisted of 335 women of reproductive age with benign ovarian tumors and who were keen on returning to work as early as possible. Surgical outcomes, postoperative pain score, postoperative satisfaction with the cosmesis score (CS), and the RTW time of the SPLS group were compared with those of the MPLS group. Besides, the RTW time and CS were calculated from the questionnaire survey by a single specialized gynecologist. Results Women who met the inclusion criteria were included in the SPLS (n = 106) and MPLS groups (n = 229). The RTW time in the SPLS group (22.13 ± 27. 06 days) was significantly shorter than that in the MPLS group (46.08 ± 57.86 days) (P < 0.001). The multivariate Cox analysis results showed that age (HR = 0.984, 95% CI, 0.971−0.997, P = 0.020), SPLS (HR = 3.491, 95% CI, 2.422−5. 032, P < 0.001), and return to normal activity time (HR = 0.980, 95% CI, 0.961−0.998, P = 0.029) were independent factors of the RTW time. Conclusions SPLS may be advantageous in terms of shortening the RTW time for women with benign ovarian tumors.